THE INFLUENCE OF UNBALANCED CURRENT IN BUS BARS ON MAGNETIC FIELD DISTRIBUTION - Milutinov, Miodrag; Kasaš Lažetić, Karolina; Spasić, Teodora; Prša, Miroslav (Journal of Energy Technology, 2025)
The analysis of magnetic field and current density distribution in the case of a three phase bus bar system with a current of 500 A is presented in this paper. The impact is investigated of the position of the neutral conductor on the magnetic field and current density distribution. The main goal of the calculations was to find the position of the neutral conductor which produces the lowest magnetic field and current density in the case of current unbalance. The numerical calculations were performed in the COMSOL Multiphysics program package on a simplified 2D model. The calculation results are presented graphically, as the diagrams of the magnetic flux and current density magnitude distribution in the three-phase bus bar system plane, are perpendicular to the system’s axis. The obtained results show that, in both cases, (current balance and current unbalance), the position of the neutral conductor influences the magnetic flux density distribution.